2011
DOI: 10.1159/000333370
|View full text |Cite
|
Sign up to set email alerts
|

VAP-1/SSAO Plasma Activity and Brain Expression in Human Hemorrhagic Stroke

Abstract: Background: Vascular adhesion protein-1 (VAP-1) is a cell surface and circulating enzyme that belongs to the semicarbazide-sensitive amine oxidase (SSAO) family, which oxidatively deaminates primary amines and is implicated in leukocyte extravasation. Our aim was to investigate the alteration of soluble VAP-1/SSAO activity in plasma samples after acute intracerebral hemorrhage (ICH) and its presence in human ICH brain tissue. Methods: VAP-1/SSAO activity was determined in plasma of 66 ICH patients and 58 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…In ICH patients, low VAP-1 independently predicted neurological improvement after 48 h (OR = 6.8) after accounting for baseline stroke characteristics [50]. This supports the finding that inhibition of VAP-1 activity in mice reduced brain cell destruction [51].…”
Section: Selection Of Blood Biomarkers In Ichsupporting
confidence: 68%
“…In ICH patients, low VAP-1 independently predicted neurological improvement after 48 h (OR = 6.8) after accounting for baseline stroke characteristics [50]. This supports the finding that inhibition of VAP-1 activity in mice reduced brain cell destruction [51].…”
Section: Selection Of Blood Biomarkers In Ichsupporting
confidence: 68%
“…Consistent with this hypothesis, soluble SSAO/VAP-1 release was observed in our stroke experimental model after OGD with reoxygenation. Interestingly, the maximal increase in plasma SSAO activity in hemorrhagic stroke patients is observed 4-6 h after symptom onset [20]. In our experimental model, soluble SSAO/VAP-1 release was mainly observed after reoxygenation, at similar time points than in humans, and matching the strongest occurrence of endothelial cell death.…”
Section: Discussionmentioning
confidence: 67%
“…Some authors have reported that 3T3-L1 adipocytes are able to release soluble SSAO by an MMP-dependent shedding mechanism [28], whereas batimastat, a broad-spectrum MMP inhibitor, avoided any SSAO release. In the periinfarcted region of stroke patients' brains, a decrease in the frequency of SSAO/VAP-1-containing vessels has been found [19,20]. In this regard, it has been suggested that mediators present in cerebrovascular pathologies such as stroke could become a stimulus to activate SSAO/VAP-1 shedding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, VAP-1 inhibition may protect against tPA-induced vascular damage by inhibiting leukocyte infiltration. Recently, the same group found plasma VAP-1/SSAO activity is increased in hemorrhagic stroke patients and may be a predictor for neurological outcome after ICH [104]. All of these clinical reports suggest VAP-1 is a potential therapeutic target for ICH-induced brain injury.…”
Section: Adhesion Cascade In Cns Disordersmentioning
confidence: 99%